Crystal data for high-pressure phases of silicon - Menoni, Carmen S., author; Spain, Ian L., author; Merkle, Larry D., author; Hu, Jing Zhu, author; American Physical Society, publisher (Colorado State University. Libraries, 1986)
X-ray-diffraction data have been obtained on Si in a diamond anvil cell to pressures of ~50 GPa. Crystallographic data are presented in phase I (cubic, diamond), II (tetragonal, β-Sn),V (simple hexagonal), VII (hexagonal close-packed), and the metastable phase III [body-centered-cubic (BC8)] and on the coexistence of the phases. Comparison is made between these data and the predictions of ab initio calculations for these structures and their equations of state.
Keywords: high-pressure phases; x-ray diffraction; silicon